Implementation of The Principle of Non-Intervention In ASEAN In The Settlement of Disputes Faced By Its Members - I Wayan Lasmawan; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Journal of Law, Politic and Humanities, 2026)
ASEAN was founded based on the Bangkok Declaration on August 8, 1967, with 11 members in the Southeast Asian region. They remain committed to the principle of non-intervention as stipulated in the 1976 Treaty of Amity and Cooperation in Southeast Asia (TAC) and the ASEAN Charter. ASEAN has developed into a major international organization and is beginning to be recognized internationally. The principle of non-intervention remains a persistent issue within ASEAN, and ASEAN leaders should consider the flexibility of this principle. This aims to assist member states facing issues, particularly humanitarian ones. This principle of non-intervention has brought ASEAN to its current level, and it is hoped that in the future, ASEAN will be able to contribute more to its fellow ASEAN members and to other organizations worldwide, thereby aligning ASEAN with its vision, mission, and objectives.